Pendampingan Moderasi Beragama dengan Strategi Growth Mindset untuk Meningkatkan Ketahanan Ideologis Siswa SMPN 2 Pasuruan - Yusuf, Achmad; Makhzuniyah, Minhah; Farida, Khusna (Jurnal Pengabdian Masyarakat, 2025)
This community service program is designed to increase the ideological resilience of SMPN 2 Pasuruan Regency students through training and mentoring of religious moderation based on a growth mindset. Using an Asset-Based Community Development (ABCD) approach, this activity focuses on utilizing local potential and involves all school stakeholders. The program, which lasts for four months (February-May 2025), involves 120 students in grades VII and VIII through various intervention methods such as interactive workshops, focus group discussions, and project-based learning. The results of the program evaluation showed significant improvements in various indicators: understanding of religious moderation increased from 78.5% to 92.3%, attitudes of tolerance between religious communities increased from 65.2% to 88.7%, and resistance to radicalism jumped from 45.8% to 81.4%. This success is supported by several key factors, including a holistic approach that combines cognitive, affective, and psychomotor aspects, as well as the active involvement of teachers, parents, and local community leaders. This program makes a real contribution in shaping the character of moderate and tolerant students, while strengthening their ideological resilience. Through the ABCD approach, all activities are designed to be sustainable by utilizing the resources available in the school and the surrounding environment. The success of this program is a model that can be replicated in other schools to strengthen religious moderation among the young generation of Indonesians.